Types of private financing of medical care by patients in Poland - Małgorzata Paszkowska (e-Finanse: Financial Internet Quarterly, 2011)
The share of privately paid medical care is steadily increasing. Polish patients pay immediately for single services and may also privately conclude the contracts for medical insurance or subscription (steady access to complex private medical care). The aim of this paper is to draw the reader's attention to the possibilities a Polish patient has of obtaining complex private medical care. The paper describes the range of services which are guaranteed for all patients insured by National Health Fund (financed from public resources) and contracts of private health insurance and medical subscription.
Keywords: K0; K12; I18; I11; 330; health service; financing; patient; National Health Fund; health insurance; medical subscription